Colleges of Education Pre-Service Teachers Perception on Career Prospects in the Field of Early Childhood Care, Development and Education - Orisadare, Hamdalah Adejoke; Lawal, Oluwaseun Temitope; Oyewumi, Nasimot Opeyemi (CV Media Inti Teknologi, 2025)
This study aims to investigate the perception and motivation of prospective teachers about ECCE as a course to plan for career future. The study adopted qualitative research design. The population consist of all pre-service teachers in 200L in the Department of ECCE in Federal Colleges of Education in Southwest, Nigeria. The sample size targeted at was 50% of 42 pre-service teachers that was meant to be proportionally selected using proportional sampling technique that was to make a total number of Twenty-One (21) pre-service teachers in Federal College of Education, Iwo, Osun State, Nigeria. The total of nineteen pre-service teachers responded to the interview which made the sample size to reduce. Three research questions guided the study. Interview questions that were sectionalized into three was used to generate data for the study. The Section A, B, and C had 3 questions each that covered pre-service teachers’ perceptions, motivations and future plan on ECCE as a profession. The data generated were analyzed using content analysis. The results shows that the respondents perceived that they have opportunities for professional growth in the field. In conclusion the pre-service teacher had positive perception on ECCE as career. The study recommends that Government and stakeholders should give more recognition to ECCE.